JJ-model isochrone set: PARSEC, MIST, and BaSTI stellar evolution - Sysoliatina, Kseniia (Universität, 2022)
This dataset contains three alternative isochrone grids generated by different stellar evolution codes - PARSEC (Padova), MIST, and BaSTI. Grids co...
Gesehen am 11.04.2022
Keywords: Forschungsdaten; Datenbank